Casa Boholana vintage houses of Bohol [Book review] - Dela Paz, Ferdinand Isidro (2013)
Access online through this link: https://journals.upd.edu.ph/index.php/asp/article/view/3968/3614
Keywords: Books -- Reviews; Bohol; Historic buildings